First we find the slope.
Slope or m =
![(Y2 - Y1)/(X2 - X1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/abko6kteet7bg3p4ugerppm8pm09p99m0j.png)
where X1 is the x-coordinate of the first ordered pair and Y1 is the y-coordinate of the first ordered pair. Same applies to X2 and Y2 for the second ordered pair.
m =
![(- 4 - (-1))/(1 - (- 2))](https://img.qammunity.org/2019/formulas/mathematics/high-school/3gysju1h62i53bpjmwr8dgqecijyae7mtt.png)
m =
![(- 4 + 1)/(1 + 2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2fms70053ag7dpmqzizcarqb2lzds0k0ps.png)
m =
![(- 3)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/pjptdmv1k5hz86eo5wqj4vh4qf5gnl87wa.png)
m = - 1
Your equation starts as y = - 1x + b or just y = - x + b
Now we plug either ordered pair into the equation and solve for b to get our complete linear function.
- 4 = - (1) + b
- 4 = - 1 + b
- 4 + 1 = b
- 3 = b
Your equation is:
y = - x - 3